Difference in the homocysteine-lowering effect of folic acid in haemodialysis patients with and without occlusive vascular disease - Descombes, Eric; Boulat, Olivier; Bersier, Louis-Félix; Fellay, Gilbert (My University, 2001)
Background. Hyperhomocysteinaemia has been identified as an independent cardiovascular risk factor and is found in more than 85% of patients on maintenance haemodialysis. Previous studies have shown that folic acid can lower circulating homocysteine in dialysis patients. We evaluated prospectively the effect of increasing the folic acid dosage from 1 to 6 mg per dialysis on plasma total homocysteine levels of haemodialysis patients with and without a history of occlusive vascular artery disease (OVD).
Methods. Thirty-nine stable patients on high-flux dialysis were studied. Their mean age was 63±11 years and 17 (43%) had a history of OVD, either coronary and/or cerebral and/or peripheral occlusive disease. For several years prior to the study, the patients had received an oral post-dialysis multivitamin supplement including 1 mg of folic acid per dialysis. After baseline determinations, the folic acid dose was increased from 1 to 6 mg/dialysis for 3 months.
Results. After 3 months, plasma homocysteine had decreased significantly by ≈23% from 31.1±12.7 to 24.5±9 µmol/l (P=0.0005), while folic acid concentrations had increased from 6.5±2.5 to 14.4±2.5 µg/l (P<0.0001). However, the decrease of homocysteine was quite different in patients with and in those without OVD. In patients with OVD, homocysteine decreased only marginally by ≈2.5% (from 29.0±10.3 to 28.3±8.4 µmol/l, P=0.74), whereas in patients without OVD there was a significant reduction of ≈34% (from 32.7±14.4 to 21.6±8.6 µmol/l, P=0.0008). Plasma homocysteine levels were reduced by >15% in three patients (18%) in the group with OVD compared with 19 (86%) in the group without OVD (P=0.001), and by >30% in none of the patients (0%) in the former group compared with 13 (59%) in the latter (P=0.001).
Conclusions. These results indicate that the homocysteine-lowering effect of folic acid administration appears to be less effective in haemodialysis patients having occlusive vascular disease than in those without evidence of such disease.
Keywords: cardiovascular disease; folic acid; haemodialysis; homocysteine; vitamins